Spatial and Spatio-Temporal Tendencies and Dependence of GDP in Selected European Countries in the Years 2001–2009 - Górna, Joanna; Górna, Karolina (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The paper presents the analysis of per capita GDP in the area of eight European countries in the period before and after their accession to the European Union. They are: the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia and Slovenia. In particular, the spatial and spatio-temporal tendencies of GDP and the dependence among the values of per capita GDP across the established regions according to the European classification system NUTS-2 are considered. The changes in time of the dependence are analyzed as well. In the investigation the ideas of spatial and spatio-temporal trends and spatial autocorrelation were used. Additionally some econometric space-time autoregressive model was specified and verified. The concept of β-convergence of NUTS-2 regions of the investigated countries in the context of spatial connections was analyzed. The data relating to the established regions was taken from the database released by Eurostat.